2023
DOI: 10.1186/s10194-023-01637-7
|View full text |Cite
|
Sign up to set email alerts
|

Ten open questions in migraine prophylaxis with monoclonal antibodies blocking the calcitonin-gene related peptide pathway: a narrative review

Abstract: The monoclonal antibodies (mAbs) blocking the calcitonin-gene related peptide (CGRP) pathway, collectively called here “anti-CGRP/rec mAbs”, have dramatically improved preventive migraine treatment. Although their efficacy and tolerability were proven in a number of randomized controlled trials (RCTs) and, maybe even more convincingly, in real world settings, a number of open questions remain. In this narrative review, we will analyze published data allowing insight in some of the uncertainties related to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 186 publications
(188 reference statements)
2
9
0
Order By: Relevance
“…Previous failures of preventive treatments, according to most trials, do not represent a negative predictor of anti-CGRP/R antibodies success, and our study confirms the evidence [ 41 , 65 ]. It should be noted that an inverse relationship between the responder rate and number of prior treatments was reported in other real-world studies [ 43 , 67 , 68 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Previous failures of preventive treatments, according to most trials, do not represent a negative predictor of anti-CGRP/R antibodies success, and our study confirms the evidence [ 41 , 65 ]. It should be noted that an inverse relationship between the responder rate and number of prior treatments was reported in other real-world studies [ 43 , 67 , 68 ].…”
Section: Discussionsupporting
confidence: 87%
“…We did not assess the pediatric (children and adolescents) population of migraineurs. The opportunity to treat these young patients with anti-CGRP/R drugs is one of the unsolved questions for the novel treatments [ 65 ]. One of the main issues is the physiological role of CGRP in bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…Now, an assessment of a patient as a responder following treatment with a gepant can be obtained within a couple of days to a week at the relevant efficacious dose. Current efforts aim to predict nonresponders and super‐responders for all modalities of CGRP‐targeting therapeutics 5 . In some cases, dose‐escalation with mAbs improves patient response, suggesting that some patients require a higher level of CGRP blockade.…”
Section: Current and Future Clinical Developments In Migrainementioning
confidence: 99%
“…For example, the combination of atogepant with onabotulinumtoxin A (NCT05216263) is currently being evaluated. Studies are also currently evaluating CGRP mAb switching between a CGRP receptor mAb and a CGRP ligand mAb 5 . These questions arise from the fundamental differences in the mechanism of action of these drugs; however, recent studies have also revealed differences in the physiological response to these drugs.…”
Section: Current and Future Clinical Developments In Migrainementioning
confidence: 99%
See 1 more Smart Citation